Application of N-Bromosuccinimide in Carbohydrate Chemistry - Bera, Smritilekha; Mondal, Dhananjoy; Chatterjee, Bhaskar (SynOpen, 2023)
This article describes the use of N-bromosuccinimide in different organic group transformations in carbohydrate chemistry. A comprehensive discussion on the synthesis of deoxysugars through selective O-benzylidene fragmentation, photobromination, halogenation, oxidation, and polymerisation of different carbohydrate moieties with the aid of N-bromosuccinimide (NBS) is presented. The use of NBS in the most significant glycosylation methods and in oligosaccharide synthesis is also discussed.
Keywords: regioselectivity; glycosylation; cleavage; N-bromosuccinimide; oxidation